CLOSING THE GAP FOR PHARMACOLOGICAL TREATMENT OF PAINFUL DIABETIC NEUROPATHY : THE POTENTIAL ROLE OF VITAMIN D - Pinzon, Rizaldy Taslim; Angela, Angela (MNJ (Malang Neurology Journal), 2022)
Painful neuropathic pain is a challenging chronic pain to treat. It is heterogeneous in symptoms and could be resistant to the available treatments regimen.  Current pharmacological treatments fail to achieve adequate pain relief in a most patients. The previous review showed that only less than 50% of patients can achieve good pain reduction with standard adjuvant treatment. The available adjuvants analgesic only focus in the symptom control, and do not interfere with the progressing damage of the nerve. Vit D insufficiency is quite frequent in type 2 diabetes patients.diabetes, particularly those with symptoms of DPN. The studies also showed that low serum vitamin D levels are an independent predictor of DPN development. Vitamin D supplementation is necessary for diabetic neuropathy patients since it promotes the synthesis of neurotrophins and neurotransmitters. Additional vitamin D therapy have big role in nerve growth factor and the regulation of neurotrophin and Ca2+ homeostasis in neurons, and provides protection for neurons in the peripheral nervous system.  In this review, we do systematically search the studies about Vitamin D for the treatment of painful diabetic neuropathic condition. We used PubMed, Cochrane, Clinical Key, and search Google Scholar for papers that used vitamin D phrases. and painful diabetic neuropathy as our major database for this  review and  we make a systematic table to explain our review. However, there is still an unmet need in the management of neuropathic pain. The unmet needs maybe caused by the gap between pharmacological treatmnet in pain reduction in painful diabetic neuropathy patients. Therefore, in this review we discuss about the potential use of vitamin D as an add-on therapy to closing the gap in the management of neuropathic pain.